Financial Soundness Indicators : Compilation Guide. (Manuals and Guides, 2006)
Financial Soundness Indicators (FSIs) are measures that indicate the current financial health and soundness of a country's financial institutions, and their corporate and household counterparts. FSIs include both aggregated individual institution data and indicators that are representative of the markets in which the financial institutions operate. FSIs are calculated and disseminated for the purpose of supporting macroprudential analysis--the assessment and surveillance of the strengths and vulnerabilities of financial systems--with a view to strengthening financial stability and limiting the likelihood of financial crises. Financial Soundness Indicators: Compilation Guide is intended to give guidance on the concepts, sources, and compilation and dissemination techniques underlying FSIs; to encourage the use and cross-country comparison of these data; and, thereby, to support national and international surveillance of financial systems.